2014
DOI: 10.1519/jsc.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Combining Normobaric Hypoxia With Short-term Resistance Training Has No Additive Beneficial Effect on Muscular Performance and Body Composition

Abstract: The aim of this study was to determine the effects of short-term resistance training combined with systemic hypoxia on muscular performance and body composition. Eighteen resistance-untrained men (21.3 ± 2.0 years, 172.7 ± 5.5 cm, 67.3 ± 9.7 kg) were matched and assigned to 2 experimental groups: performing 6 weeks of squat exercise training under normobaric hypoxia (H, FiO2 = 15%) or normoxia (N). In both groups, subjects performed 3 weekly sessions (a total of 18 sessions) of 3 sets of back squat at 10-repet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 21 publications
4
56
0
Order By: Relevance
“…These studies are summarized in [11,17]. However, other investigations using similar training loads but with extended inter-set recovery intervals (90-120 s) have demonstrated no added benefit for training under hypoxia [12,13]. Although it is too early to make definitive recommendations based on only these investigations, we hypothesize that low-and moderate-load IHRT might only provide added benefit when relatively brief inter-set rest periods are used.…”
Section: Conflicting Results Of Ihrt Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…These studies are summarized in [11,17]. However, other investigations using similar training loads but with extended inter-set recovery intervals (90-120 s) have demonstrated no added benefit for training under hypoxia [12,13]. Although it is too early to make definitive recommendations based on only these investigations, we hypothesize that low-and moderate-load IHRT might only provide added benefit when relatively brief inter-set rest periods are used.…”
Section: Conflicting Results Of Ihrt Studiesmentioning
confidence: 94%
“…However, if the inter-set recovery interval is extended past these durations, the hypoxia-mediated alterations in 12 energy system contributions and subsequent metabolic stress are likely to be attenuated. This is highlighted by recent research from Ho, et al [12] and Kon, et al…”
Section: Considerations For Training Programsmentioning
confidence: 86%
See 1 more Smart Citation
“…It is therefore likely that the three-minute inter-set recovery employed in the current study was sufficient to allow nearcomplete PCr resynthesis. To this point, a recent investigation using moderate-intensity IHRT (10RM) with longer inter-set rest periods than typically used at that intensity (120 s) has demonstrated no added hypertrophic or strength benefit for IHRT (15). These results contrast those of Nishimura et al (25), and could indicate that longer inter-set rest intervals attenuate any hypoxia-mediated increases in metabolic stress, and subsequent downstream anabolic responses.…”
Section: Discussionmentioning
confidence: 96%
“…No differences between conditions in the theoretical maximal strength were reported by Kurobe’s team, but 1RM estimates in high repetition tests to failure (10RM, ~75% 1RM) may be unreliable due to fatigue and mechanical stress [53, 54]. Contrary to these findings, Ho et al [15] concluded that 6 weeks of short-term resistance training (3 sets of 10RM; 2 min rest) under NH (15% FiO 2 ) offered no additional benefit to muscular performance or body composition. Likewise, Kon et al [16] observed no strength or muscle size gains in response to bench press and leg press (16 sessions of 5 sets × 10 repetitions at 70% 1RM; 90 s of rest) though they did detect enhanced skeletal muscle endurance and angiogenesis.…”
Section: Hypertrophy Trainability In Conditions Of Hypoxiamentioning
confidence: 99%